ESTUTI: Ethnomedicine and Transformation of Ice Cream to Prevent Stunting Using Family Medicinal Plants in Tanggamus - Diah Kartika Putri; Fina Aulika Lestari; Taufiki Miftausakina; Amalia Siti Nurazizah; Adi Saputra; Vicko Suswidiantoro; Wina Safutri (Universitas Aisyah Pringsewu, 2025)
The stunting prevalence rate for Lampung Province based on the 2022 SSGI averages 15.2% and Tanggamus Regency is ranked fourth with the highest stunting prevalence, namely 20.4%. This research aims to use TOGA as a spearhead for treating stunting in toddlers using Moringa leaves and ginger rhizomes. Moringa leaves (Moringa Oleifera Lam.) can be used as a potential alternative source of protein and calcium to meet children's nutritional needs. The ESTUTI formulation is divided into 3 formulations with differences in Moringa leaf extract and ginger, namely 25gr/100ml water, 50gr/100ml water, and 75gr/100ml water. Tests in this research include organoleptic tests, hedonic tests and melting point tests. The results show that the most preferred